Geographical Indications in Promoting Sustainable Trade Practices and Achieving Sustainable Development Goals - Tsymbalova, Nadia (2025)
Regarded as an intellectual property tool promoting products’ regional embeddedness, geographical indications (GIs) have been receiving increased attention in the context of the global pursuit of the integration of sustainability considerations in international trade. Approaching the question of the role of GIs in promoting sustainable trade practices through the framework of the UN’s Sustainable Development Goals (SDGs), this thesis begins by establishing the theoretical background on the connections between GIs and SDGs, examining the economic, social, cultural, and environmental consequences of GI protection. Subsequently, using primary data, the relationship between the prevalence of geographical indications in a region and its socioeconomic development is explored, using a set of indicators relating to SDGs. Thereupon, policy recommendations are proposed, integrating scholars’ findings on best practices in the adoption of GI schemes and discussing any potential limitations to the effectiveness of such initiatives. Thus, this thesis aims to provide a balanced view of the potential of GIs in fostering ethical practices in global commerce.